The Impact of Green Supply Chain and Digitalization on Environmental Sustainability in Healthcare Clinics: The Moderating Role of Digitalization - Syahfitri, Rini; M Zai, Yovita Yulia; Agustini, Cynthia (JTI: Jurnal Teknik Industri, 2025)
Green Supply Chain Management (GSCM) has received increasing attention as a strategy to minimize the environmental impact of the healthcare supply chain. Not only GSCM, but digitalization practices are also believed to improve efficiency and reduce operational costs. This study aims to examine the role of digitalization as a reinforcing factor in the effectiveness of GSCM practices for environmental sustainability. This research began with hypothesis preparation, which consisted of three hypotheses. Furthermore, data on the assessment of the relationship between digitalization, green supply chain, and environmental sustainability were collected through questionnaires to Health Clinics in Padang. Data processing was carried out using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with SmartPLS 3.0. The processing stages consist of structural model design, measurement model design, path diagram design, model evaluation, hypothesis testing, and IPMA analysis. From the processing results, digitalization and a green supply chain both make significant contributions to environmental sustainability at the Padang Health Clinic. Furthermore, based on IPMA's analysis, the implementation of green supply chain aspects and digitalization in the field has reached 69%. Nonetheless, there is still room for improvement to achieve better environmental sustainability. Therefore, to achieve environmental sustainability, health clinics need to emphasize and implement green supply chain and digitalization indicators.  Keywords: Digitalization, Sustainability, Green Supply Chain, Healthcare, PLS-SEM